Leadership insights for wizards and witches - Simha, Aditya (Bingley, U.K. : Emerald Publishing Limited, 2022)
Popular culture can help us think creatively and teach us the best ways to use our imagination. Leadership Insights for Wizards and Witches outlines various leadership styles, theories, and concepts through the imaginative lens of J.K. Rowling's magical world - from ethical, servant, and authentic leadership, to power, influence, and persuasion. Combining the immersive and enchanting context of the series with the scholarly discipline of leadership, Simha teaches key theories using examples of characters and situations familiar to fans. Leadership Insights for Wizards and Witches encourages readers to consider how they themselves can approach personal and organizational problems by finding solutions using insights and perspectives gathered from the discipline of leadership. Readers will gain a vital understanding of how not to lead for a holistic mastery of leadership. Leadership Insights for Wizards and Witches harnesses surprisingly relatable examples from the renowned mystical stories and movies to inform a variety of readers, ranging from high school students to undergraduate students and professional practitioners - and of course fans everywhere - regardless of professional backgrounds and experience. The Exploring Effective Leadership Practices through Popular Culture series breaks down leadership theories, making them clearer, manageable, and easier to put into practice.
Chapter 1. Introduction -- Chapter 2. Personality, culture, and leadership -- Chapter 3. Cognitive and emotional intelligence and leadership -- Chapter 4. Behavioral and style approaches to leadership -- Chapter 5. Contingency and situational leadership -- Chapter 6. Leader power and politics -- Chapter 7. Leader influence & persuasion -- Chapter 8. Authentic leadership -- Chapter 9. Ethical leadership -- Chapter 10. Servant leadership -- Chapter 11. The dark (and bright) sides of charismatic leadership -- Chapter 12. Transactional and transformational leadership -- Chapter 13. Self and shared leadership -- Chapter 14. Leadership succession -- Chapter 15. An epilogue of sorts.
Includes bibliographical references and index.
Keywords: Leadership; Business & Economics -- Leadership; Management: leadership & motivation